Aid and growth: What meta-analysis reveals - Tseday Jemaneh Mekasha; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Some recent literature in the meta-analysis category where results from a range of studies are brought together throws doubt on the ability of foreign aid to foster economic growth and development. This paper assesses what meta-analysis has to say about the effectiveness of foreign aid in terms of the growth impact. We re-examine key hypotheses, and find that the effect of aid on growth is positive and statistically significant. This significant effect is genuine, and not an artefact of publication selection. We also show why our results differ from those published elsewhere.
Keywords: F35; O1; O4; 330; aid and growth; meta-analysis; heterogeneity and publication bias; Entwicklungshilfe; Wirtschaftswachstum